LINGKUNGAN KERJA, BEBAN KERJA DAN BURNOUT PADA KARYAWAN PT. NIPSEA PAINT AND CHEMICAL BANJARMASIN - Tetty Flora Sitinjak; Rizky Nastiti (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2022)
ABSTRACT This study aims to determine the effect of the work environment and workload on burnout on employees of PT. Nipsea Paint and Chemical Banjarmasin. This study employed quantitative methods by distributing questionnaires to 60 employees of PT. Nipsea Paint and Chemical to determine the burnout level of the employees. By using multiple linear regression method, the data obtained were analyzed. The results of the study revealed that the work environment had a negative and significant effect on burnout. This meant that if the comfort of the work environment was increased, the employee burnout would decrease. Meanwhile, workload had a positive and significant effect on burnout of employees of PT Nipsea Paint and Chemicals Banjarmasin. This meant that if the workload increased, employee burnout would also increase. Keywords: work environment, workload, burnout